(untitled) (Journal of Finance, Business and Management Studies, 2022)
The COVID-19 pandemic has made a new era in the world & Still we figure out the consequences in different aspects of our lifestyle. The food supply chain and the food industry don’t comprise an exception. This research paper focuses on Green supply chain management practices such as Green purchasing, Green awareness and Green implementation among employees at Hotels. The respondents are 25 hotel employees selected from Food & Beverage, purchasing, receiving and inventory departments. Respondents are determined by the characteristics of their knowledge and availability of the supply chain management activities that are interrelated with departments in hotels. The findings show that respondents have a positive attitude towards the supply chain management practices in hotels. The study has identified the difficulties of adopting green practices across the hotel also. Results also provide insight and direction for adopting green practices across the supply chains of hotels worldwide.